A hydraulic control system integrating adaptive and PWM algorithms for hydro-mechanical continuously variable transmission - Cui, Jingjun (Frontiers in Mechanical Engineering, 2024)
IntroductionWith the development of technology, the hydraulic control system for hydro-mechanical continuously variable transmission has also made rapid progress. However, the traditional control system for hydro-mechanical continuously variable transmission has drawbacks such as efficiency loss and slow response speed. The study fused the adaptive and pulse width modulation algorithms to solve these problems effectively, and they were applied to the hydraulic mechanical continuously variable drive control system.MethodFirst, the study analyzed the continuously variable transmission control of hydraulic machinery and designed the control scheme on the basis of the analysis. Then, a new scheme fusing adaptive and pulse-width modulation algorithms was proposed on the basis of the control scheme. Finally, simulation experiments and practical tests were carried out to verify the performance of the control scheme.ResultsThe results showed that the time to reach the maximum pressure was 2.15 s when the volume of the pilot valve cavity was 5 × 109/L. When the oil flow rate was 70 L/min, the corresponding maximum and minimum values of the main oil circuit pressure were 1.63 MPa and 0.37 MPa, respectively. The time to reach the maximum value of the pressure was 2.05 s, respectively. These values were in line with the design requirements and were better than the comparison values.DiscussionThese results confirm that the system has important theoretical and practical significance, which has a positive promoting effect on the development of the hydraulic machinery industry. This article aims to provide a new approach for research and application in related fields.